PENGGUNAAN UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI TERHADAP TINDAK PIDANA DI BIDANG PERBANKAN - Yusriadi (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2020)
This article discusses relating to "The use of laws eradicating criminalacts of corruption against criminal acts in the field of banking," As for theemphasis of the problem in this article is how a criminal act committed by bankscan be categorized as a criminal act of corruption, and how the process theapplication of the precautionary principle in banking (Prudencial Banking) can beapplied in corruption. In this article it is illustrated that the use of the CorruptionCrime Eradication Act in solving the problem of bad credit at state-owned banksis more precise by looking at the reasons for the bad credit. When a party isindeed proven to have acted that deviates from the original purpose of providingthe credit and fulfilling the elements against the law, enriching oneself / others /corporation, and harming the state finances / the economy of the country, it isappropriate to apply the Corruption Eradication Act. principles in banking law andbased on the applicable laws and regulations, the perpetrators of criminal acts inthe banking sector (owners / shareholders, management or bank employees) mustbe responsible for irregularities in banking operations that meet the elements ofcriminal acts in the banking sector and the elements of acts criminal corruption.